Astrocytes are involved in the formation of corpora amylacea-like structures from neuronal debris in the CA1 region of the rat hippocampus after ischemia - Riew, Tae-Ryong; Hwang, Ji-Won; Jin, Xuyan; Kim, Hong Lim; Jung, Sharon Jiyoon; Lee, Mun-Yong (Frontiers in Cellular Neuroscience, 2023)
Recently, we demonstrated that the corpora amylacea (CA), a glycoprotein-rich aggregate frequently found in aged brains, accumulates in the ischemic hippocampus and that osteopontin (OPN) mediates the entire process of CA formation. Therefore, this study aimed to elucidate the mechanisms by which astrocytes and microglia participate in CA formation during the late phase (4–12 weeks) of brain ischemia. Based on various morphological analyses, including immunohistochemistry, in situ hybridization, immunoelectron microscopy, and correlative light and electron microscopy, we propose that astrocytes are the primary cells responsible for CA formation after ischemia. During the subacute phase after ischemia, astrocytes, rather than microglia, express Opn messenger ribonucleic acid and OPN protein, a surrogate marker and key component of CA. Furthermore, the specific localization of OPN in the Golgi complex suggests that it is synthesized and secreted by astrocytes. Astrocytes were in close proximity to type I OPN deposits, which accumulated in the mitochondria of degenerating neurons before fully forming the CA (type III OPN deposits). Throughout CA formation, astrocytes remained closely attached to OPN deposits, with their processes exhibiting well-developed gap junctions. Astrocytic cytoplasmic protein S100β, a calcium-binding protein, was detected within the fully formed CA. Additionally, ultrastructural analysis revealed direct contact between astroglial fibrils and the forming facets of the CA. Overall, we demonstrated that astrocytes play a central role in mediating CA formation from the initial stages of OPN deposit accumulation to the evolution of fully formed CA following transient ischemia in the hippocampus.